In my dreams I hold a knife : a novel - Winstead, Ashley (Sourcebooks Landmark, 2021)
"Jessica Miller plans to triumphantly return to Duquette University for her ten year reunion festivities. She's the most successful out of her entire group of friends, and she's ready to flaunt her achievements...even though her "friend group," known on campus as the East House Seven, doesn't really exist anymore. Ten years ago, Heather, one of their own, was murdered, fracturing the once close knit group. And then another friend was accused of committing the vile act, shattering whatever friendly feelings remained. Jessica thinks she's coming back to campus to bask in a wave of glory. She and her friends have no idea that someone has set an elaborate trap to catch the real killer and close the cold case for good."--